The saddest words : William Faulkner's Civil War - Gorra, Michael Edward (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2020)
"How do we read William Faulkner in the twenty-first century? asks Michael Gorra, one of America's most preeminent literary critics. Should we still read William Faulkner in this new century? What can his works tell us about the legacy of slavery and the Civil War, that central quarrel in our nation's history? These are the provocative questions that Michael Gorra asks in this historic portrait of the novelist and his world. Born in 1897 in Mississippi, Faulkner wrote such iconic novels as Absalom, Absalom! and The Sound and the Fury, creating in Yoknapatawpha County the richest gallery of characters in American fiction, his achievements culminating in the 1949 Nobel Prize in Literature. But given his works' echo of "Lost Cause" romanticism, his depiction of black characters and black speech, and his rendering of race relations in a largely unreconstructed South, Faulkner demands a sobering reevaluation. Interweaving biography, absorbing literary criticism, and rich travelogue, The Saddest Words recontextualizes Faulkner, revealing a civil war within him, while examining the most plangent cultural issues facing American literature today"--